ANALISIS MAKNA GERAK TARI BAKONCONG SUKU DAYAK SALAKO KECAMATAN SAJINGAN BESAR KABUPATEN SAMBAS - Janita, Angen Dea; Istiandini, Winda; Tindarika, Regaria (Universitas Tanjungpura, 2023)
This research is motivated by the interest of researchers about the Bakoncong dance movement. The uniqueness of this dancers is that the dancers are moved to dance by the spirit of an angel. In Bakoncong dance, there is Bajahatn movement, Ngalambe Rajaki and Jentera. Bakoncong dance is a medium for delivering prayers to Jubata which has a deep meaning, related to the life of the Salako Dayak community. The purpose of this study is to describe and analyze the meaning of the Bakoncong dance movements. The research uses descriptive analysis method, qualitative research form, ethnochoreology and semiotics research approaches, research data sources from observations, interviews, and documentation of resource persons in Felicia Conen, Ucel Benidikta and Epensius. The tecnique of testing the validity of the research data uses triangulation of sources and extension of observations, then the data analysis techniques is to describe and analyze the meaning of Bakoncong dance movements. The results of the data analysis of this study indicate that the movement of the Bakoncong dance contains the meaning of prayers that are said by the Salako Dayak community given to Jubata so that hopes and wishes prayers can be fulfilled.